NETWORK GEOGRAPHIC EDUCATION: THE CONTRIBUTION OF THE WE PROPOSE! PROJECT - Nunes, Sérgio Claudino Loureiro; de Araújo, Raimundo Lenilde; Mello, Márcia Cristina de Olievira [UNESP]; Silva, Adilson Tadeu Basquerote; Lastória, Andrea Coelho; Filho, Odairo Ribeiro de Carvalho (Ludomedia Unipessoal Lda, 2023)
The results of the We Propose! Project are presented, which focuses on the organization of the Geography curriculum based on the identification of local problems by the students of the schools involved. Since 2011, this project has been implemented by the Institute of Geography and Spatial Planning of the University of Lisbon/IGOT-ULisboa, mobilizing schools from all over the country, in the framework of the discipline of Geography, with a view to have an effective commitment to the community. Since 2014, the project has gained international momentum in Ibero-America and beyond. Its methodological proposal is to challenge students to identify relevant local problems, develop field work on them, and point out possible solutions. The learning will be centered on the students themselves. It is expected that the students develop territorial citizenship, understood as responsible participation in decision-making about the problems of the spatially-based locality.
EDUCAÇÃO GEOGRÁFICA EM REDE: A CONTRIBUIÇÃO DO PROJETO NÓS PROPOMOS (NP)!
Keywords: Geographic education; Project We propose!; Territorial citizenship